Exploring the Mechanism of Isoliquiritigenin on Lung Cancer Based on Network Pharmacology and Molecular Docking - Weng, Guibin; Fang, Weimin; Su, Weikun; Chen, Lin; Liao, Menglin; Lin, Yijin (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: This study aims to explore how Isoliquiritigenin (ISL) combats lung cancer by using network pharmacology and molecular docking techniques. Materials and Methods: We used multiple databases to find ISL-related targets and lung cancer-associated genes, followed by enrichment analysis using the Cluster Profiler package. Network analysis via the STRING database and Cytoscape illuminated the protein-protein interaction landscape. The Kaplan-Meier plotter evaluated the prognostic relevance of gene expression. Molecular docking assessed the binding affinity of ISL to key proteins. Results: Our study identified 412 ISL targets and intersected these with 15,373 lung cancer-related genes, pinpointing 232 genes of potential therapeutic interest. Enrichment analysis revealed significant pathways, including those related to cancer and cellular signaling. Network analysis underscored key nodes such as AKT1, TNF, EGFR, HSP90AA1 and ESR1. Molecular docking confirmed substantial binding affinities, suggesting inhibitory capabilities against these proteins. Discussion: The enrichment analysis implicated ISL in modulating a spectrum of biological processes, particularly those involved in cell communication and systemic biological functions. Key genes identified via network analysis could serve as novel targets for intervention. Molecular docking emphasized ISL's potential as a multi-target inhibitor, thus reinforcing its candidacy as a promising therapeutic agent against lung cancer.
Keywords: ISL; Isoliquiritigenin; Lung Cancer; Molecular Docking; Network Pharmacology; Protein-Protein Interactions